ANALYSIS OF THE INCOME OF OFFLINE STORE MERCHANTS AT THE GORONTALO CITY CENTRAL MARKET AFTER THE RISE OF ONLINE SHOPS - Alinti, Fikri; Bokiu, Zulkifli; Yusuf, Nilawaty (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the income of offline store traders in the Gorontalo City Central Market after the emergence of Online Shop. The main problem raised is to examine the impact of the rise of online shops on the financial condition of traditional traders. This study uses a qualitative method with a descriptive approach to explore the experiences and deep perceptions of the affected traders. The research informants consisted of 5 shop owners (textiles, shoes, and cosmetics) in the Gorontalo City Central Market who have been running their businesses for many years. The results of the study consistently show that the presence of online shops has had a very significant negative impact on the financial condition of offline store traders in the Gorontalo City Central Market.Before the rise of online shops (around 2018 and below), offline store sales conditions were very good and stable, with an average daily turnover ranging from IDR 1,000,000 to IDR 2,000,000, even reaching up to IDR 5,000,000 during the high season. After the emergence of online shops (around 2018-2020), merchants' income experienced a sharp decline.